Epithelial Ovarian Cancer Treated by Platinum or Platinum Analogue with Cyclophosphamide : Experience in Ramathibodi Hospital - Vasant Linasmita (2018)
This study presented the outcome of 92 EOC patients treated by platinum or platinum analogue with cyclophosphamide from January 1, 1993 to December 31, 1995. There were 77 evaluable patients. The follow-up ranged from 4 - 42 months (median 14 months). The over all 3-year survival was 64 per cent and the median progression-free interval was 16 months for the whole group. There was no significant difference in survival between patients who received cisplatin and those who received carboplatin (P=0.093). Patients who underwent optimal debulking surgery had significantly longer progression-free interval (P=0.001) than those who had suboptimal surgery. Fifty four per cent of patients with clear cell carcinoma died of the disease. Patients who received cisplatin had a drop out rate while on therapy more often (24% vs 5.3%) than that of carboplatin. Toxicities from chemotherapy were moderate but manageable.